Relationship Between Organizational Ergonomics and Work Motivation in The Ministry of Religion Binjai: Relationship Between Organizational Ergonomics and Work Motivation - Anggi Pratama Sagala; Gerry Silaban; Umi Salmah (Jurnal Kesehatan dr. Soebandi, 2023)
The work system applied to government agencies is influenced by several ergonomic aspects involved in the process. This includes interactions between workers and the work type, tools used, internal and external environmental conditions, and related organizations. The lack of application of organizational ergonomics to employees causes low work motivation among employees. This study aimed to determine the relationship between organizational ergonomics and the work motivation of employees at the Ministry of Religion Binjai. This study was quantitative with a cross-sectional approach. The population was all employees at the Office of the Ministry of Religion Binjai, totaling 62 people. The sampling technique was total sampling. Data was collected using a questionnaire and analyzed using the product-moment correlation test. The results showed that there was a relationship between vertical communication, and work motivation (p=0.020), there was a relationship between horizontal communication and work motivation (p=0.000), there was a relationship between training and work motivation (p=0.000), there was a relationship between teamwork and work motivation (p=0.000). The variable most related to the very strong category was teamwork, with a correlation coefficient (r) of 0.901. Employees should be more open and instill a sense of trust among employees towards the work being done, especially by establishing good communication so that good teamwork can be created to increase employee motivation. Keyword: Organizational Ergonomics, Work Motivation, Minister of Religion